Dampak Penggunaan Sosial Media Terhadap Variasi Penggunaan Bahasa Indonesia di Kalangan Remaja : Studi Deskriptif - Zafira, Kamilah Sarah (Universitas Negeri Padang, 2024)
This study aims to analyze the impact of social media on the variation of Indonesian language use among teenagers. Utilizing a qualitative descriptive approach, the research explores how social media influences the use of slang, abbreviations, and the mixing of Indonesian with foreign languages. Data were collected through surveys and group discussions with teenagers aged 15 to 20. The findings indicate that social media plays a role in enriching teenagers' vocabulary, introducing new terms, and facilitating identity expression through slang. However, on the other hand, social media also brings negative effects, such as a decline in formal language skills and a tendency to use non-standard grammar. This study provides important insights into the challenges of maintaining the quality of the Indonesian language in the digital era and highlights the need for awareness of the importance of formal language use in specific contexts, such as education.